2019
DOI: 10.1590/1414-431x20198204
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and prognostic ability of the SARC-F questionnaire and Ishii's score in the screening of sarcopenia in geriatric inpatients

Abstract: Sarcopenia remains poorly managed in clinical practice due to the lack of simple and accurate screening tools. This study aimed to identify the cutoff values of the SARC-F questionnaire and Ishii's score using the variables age, grip strength, and calf circumference in older inpatients in China to compare the accuracy of the two methods and to explore their predictive ability for adverse outcomes (rehospitalization, falls, fracture, and death). Hospitalized patients (n=138) aged ≥60 years were included. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 34 publications
6
33
2
6
Order By: Relevance
“…Applying the Youden index to our study population, we showed that the ideal SARC-F cut-off for sarcopenia diagnosis is lower than the score proposed in the validation study [ 7 ]. However, this result is in line with a previous report from Li et al [ 22 ] and was expected, considering that our study population, recruited in a geriatric acute care ward, is older and has larger burden of diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Applying the Youden index to our study population, we showed that the ideal SARC-F cut-off for sarcopenia diagnosis is lower than the score proposed in the validation study [ 7 ]. However, this result is in line with a previous report from Li et al [ 22 ] and was expected, considering that our study population, recruited in a geriatric acute care ward, is older and has larger burden of diseases.…”
Section: Discussionsupporting
confidence: 93%
“…A total of 21,855 individuals were included (20 to 3997 individuals per article), with a weighted mean age of 63.3 AE 14.6 years (range: 54.7 AE 11.3 years to 84.6 AE 9.17 years) and of which 61.3% were females (Table 1). Populations included community-dwelling older adults (n ¼ 1,618,957 individuals), 37e40,47e51,56,57,59e61, 63,64 geriatric inpatients (n ¼ 51,598 individuals), 41,43,44,53,54 geriatric outpatients (n ¼ 5802 individuals), 42,45,46,58 nursing home residents (n ¼ 2357 individuals), 62,65 and long-term care residents (n ¼ 1141 individuals). 52 Fifteen articles included individuals from Asia, 8 articles from Europe, 3 articles from South America, and 3 articles from North America.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…20 A study involving 126 hospitalized older patients of Chinese descent showed that SARC-F questionnaire was an independent predictor of hospital readmission in 1 year (HR = 4.23; 95% CI, 2.12-9.79). 21 Another study, using SARC-F, showed a higher 4year rate of general hospitalizations in patients with suggestive of sarcopenia (65.6% vs 40%), compared with those without the condition. 15 No article was identified in the literature that assessed the association between sarcopenia screening and in-hospital mortality, so the prognostic value of SARC-CalF in predicting in-hospital mortality requires further investigation.…”
Section: Discussionmentioning
confidence: 95%